Investigating the relationship between social media usage duration and academic success among Muslim students using data science process - Ali Hassan, Ahmed Ramadan; Hassan, Raini (KICT Publishing, 2024)
This study explores the relationship between social media use and academic success among Muslim students. By analyzing social media usage patterns and potential correlations with academic performance, the research addresses key questions on how social media impacts this student group. A survey distributed to 222 Muslim students reveals a modest negative correlation between prolonged social media usage and academic performance, particularly for those spending over five hours daily on social media. The study concludes that social media can be a significant distraction, but its impact varies, highlighting the need for tailored strategies to mitigate potential negative effects on academic success.